Income Spreading Mechanisms in Common Property Resource Karanila System in Kerala's Fishery - John Kurien A J Vijayan (Economic and Political Weekly July 15, 1995, 1995)
An important feature of small-scale fishing communities in developing countries is community-evolved mechanisms to ensure that the resources, livelihood opportunities and revenues from the common property fishery are spread as widely as possible in the whole community. This article examines the case of an income spreading mechanism which has been practised in the coastal encircling net fishery of Kerala for about half a century. It shows how a combination of inappropriate technology choices coming in the wake of free market policies, and a now increasingly common pattern of state patronage of rural producers, often combine to create open access conditions in common property resources and thus put eminently desirable communitarian systems of sharing and caring under great strain.